Unfit for the future? the need for moral enhancement - Persson, Ingmar; Savulescu, Julian (Oxford : Oxford University Press, 2012)
This text argues that the future of our species depends on radical enhancement of the moral aspects of our nature. Population growth and technological advances are threatening to undermine the conditions of worthwhile life on Earth forever. We need to modify to deal with this challenge.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Moral motivation; Environmental ethics; Bioethics